Setting up an adult congenital heart programme - Webb, Gary D.; Veldtman, Gruschen R. (SA Heart Journal, 2017)
With the growing number of adult patients with congenital heart defects in the developing world, many institutions and practice groups are beginning or growing their adult congenital heart disease (ACHD) programmes. In this paper, we review: ■ Practical considerations in establishing a clinic (Where will your patients come from? How many new referrals annually can you anticipate?); ■ Transition and transfer challenges (can you avoid the loss to care of children with moderate and complex congenital heart defects? Is there an agreed age of transfer policy? Is there an available and effective transition process?); ■ Institutional considerations (do you really have the support of your institution? Where should your program be located? Where will you admit your inpatients?); ■ Patient care imperatives (how will you commit to excellent patient care? How will you meet the needs of your patients? Clearly designate which patients you will need to refer out and to which services they will be referred); ■ The composition of the ACHD team (begin with two ACHD cardiologists and skilled echocardiography, consider a mix of pediatric trained and adult trained cardiologists, grow from there in a modular fashion if you can to include more multidisciplinary team members, and duplicate essential service positions); and ■ Organisation and accreditation of ACHD care (ACHD services need to be managed differently than pediatric services across the full diagnostic and treatment clinical spectrum).